Comparison of Epidural Steroid Injection Efficiency with Two Different Doses in Radiculopathies Associated with Lumbar Disc Herniation - GÜNDÜZ, OSMAN HAKAN (ELSEVIER SCIENCE INC, 2019)
OBJECTIVE: Transforaminal epidural steroid injections (TFESIs) have been increasingly used in the treatment of lumbar radicular pain resistant to conservative modalities. Although different steroids can be used at different doses, the minimally effective steroid dose should be used to reduce side effects. The present retrospective study examined and compared the efficacy of 40 mg and 80 mg of methylprednisolone in TFESIs. METHODS: We included 67 patients who had undergone unilateral L5-S1 TFESIs under fluoroscopic guidance in the present study. Assessments were conducted at baseline and at 1 hour, 3 weeks, and 3 months after the TFESIs. The Short-Form 36-item Health Survey, Numeric Rating Scale, Oswestry Disability Index, and Istanbul Low Back Pain Disability Index were used as outcome measures. RESULTS: The present study evaluated 33 patients who had undergone TFESIs with 40 mg of methylprednisolone and 34 patients who had undergone TFESIs with 80 mg of methylprednisolone. Although no statistically significant differences were found between the 2 groups' outcome measures, both groups showed significant improvements in pain, disability, and quality of life at 3 weeks and 3 months after treatment. CONCLUSIONS: TFESIs with 40 mg and 80 mg are effective for the treatment of pain that results from lumbar disc herniation. They also positively affect patients' disability and quality of life. However, neither steroid dose was more efficient than the other dose. Therefore, we believe the smaller dose should be preferred to reduce the potential side effects of steroids.
Keywords: Epidural; Injection; Methylprednisolone; Radiculopathy; Transforaminal; CHRONIC LOW-BACK; RADICULAR PAIN; NONPARTICULATE CORTICOSTEROIDS; DOUBLE-BLIND; EFFICACY; METHYLPREDNISOLONE; DEXAMETHASONE; INTERLAMINAR; PARTICULATE